-7(2x-6)+3=15+1x

Simple and best practice solution for -7(2x-6)+3=15+1x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(2x-6)+3=15+1x equation:



-7(2x-6)+3=15+1x
We move all terms to the left:
-7(2x-6)+3-(15+1x)=0
We add all the numbers together, and all the variables
-7(2x-6)-(x+15)+3=0
We multiply parentheses
-14x-(x+15)+42+3=0
We get rid of parentheses
-14x-x-15+42+3=0
We add all the numbers together, and all the variables
-15x+30=0
We move all terms containing x to the left, all other terms to the right
-15x=-30
x=-30/-15
x=+2

See similar equations:

| X+52=8x-39 | | 20.000=426x+5356 | | -4(1+3n)=-64 | | -7x+52=5(x-4) | | 4x-(8x-24)=12 | | 10m=4.39 | | 3x+3=6x-12+6 | | 5x-(8-2x)=20 | | -2b+9=17 | | 3x+10x-2+x=5(3x-1) | | x+5=-10+4x | | 38=5x-3 | | -3(5g-7)=81 | | 47=2f=3 | | f(11)=5(11)-21= | | 180=16x-4=4+4x | | 8x+23=5x+1 | | 4w+2=-42 | | 5x+2=35x-1 | | 5(x+2)-3=3x+8x+7 | | x/2-20=13 | | -y/12=10 | | -2x+10=5x+3 | | 1/2(w-5)=23 | | -94=-8-2(7r+1) | | 10+5*2x+8=60 | | 10x-20=30x= | | 8=7+m/8 | | 2x2+13x=11 | | x–15=–31 | | 5(x=2)-3=3x=8x+7 | | 5x+7=8x+71 |

Equations solver categories